High background rates of positive tuberculosis-specific interferon-γ release assays in a low prevalence region of UK: a surveillance study - Hinks Timothy SC; Varsani Nimu; Godsiff David T; Bull Thomas C; Nash Katherine L; McLuckie Lisa; Maule Catherine; Flower Tessa; Warley Anthony (BMC Infectious Diseases, 2012)
Abstract Background Background rates of latent tuberculosis infection in low prevalence regions of Britain are unknown. These would be valuable data for interpreting positive IGRA results, and guiding cost-benefit analyses. The management of a large outbreak of tuberculosis occurring in a rural district hospital provided an opportunity to determine the background rates and epidemiology of IGRA-positivity amongst unselected hospital patients in a low-prevalence region of U.K. Methods As part of a public health surveillance project we identified 445 individuals exposed to the index cases for clinical assessment and testing by a TB-specific interferon-γ release assay (IGRA): T-Spot.TB. Uniquely, an additional comparator group of 191 age-matched individuals without specific recent exposure, but with a similar age distribution and demographic, were recruited from the same wards where exposure had previously occurred, to undergo assessment by questionnaire and IGRA. Results Rates of IGRA positivity were 8.7% (95%CI, 4.2-13, n=149) amongst unexposed patients, 9.5%(3.0-22, n=21) amongst unexposed staff, 22%(14–29, n=130) amongst exposed patients, 11%(6.1-16, n=142) amongst exposed staff. Amongst the individuals without history of recent exposure to the outbreak, IGRA-positivity was associated with prior TB treatment (OR11, P.04) and corticosteroid use (OR5.9, P.02). Background age-specific prevalences of IGRA-positivity amongst unexposed individuals were: age <40 0%(N/A), age 40–59 15%(12–29), age 60–79 7.0%(1.1-13), age≥80 10%(5.9-19). Conclusions Background rates of IGRA-positivity remain high amongst unselected white-Caucasian hospital inpatients in U.K. These data will aid interpretation of future outbreak studies. As rates peak in the 5th and 6th decade, given an ageing population and increasing iatrogenic immunosuppression, reactivation of LTBI may be a persistent hazard in this population for several decades to come.